2013
DOI: 10.1002/dys.1460
|View full text |Cite
|
Sign up to set email alerts
|

Weaknesses in Semantic, Syntactic and Oral Language Expression Contribute to Reading Difficulties in Chinese Dyslexic Children

Abstract: The present study examined the role of weaknesses in some language skills for the reading difficulties among Chinese dyslexic children. Thirty Chinese dyslexic children were compared with 30 chronological age (CA) controls and 30 reading-level (RL) controls on a number of language and reading measures. The results showed that Chinese dyslexic children performed significantly worse than the CA controls but similarly to the RL controls in many of the linguistic measures except that the dyslexic group also perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 100 publications
(124 reference statements)
0
19
1
Order By: Relevance
“…To address both questions, we implemented a videogame-based motor training protocol and assessed the appraisal of actions in narratives through discourse-level processes subsuming multiple operations (e.g., word access, syntactic parsing, semantic integration, memory retrieval). Strategically, our intervention was aimed at dyslexic children, whose potential comprehension deficits 3 , 4 could give room to post-training improvements. As in previous research on text-level action appraisal 5 , our approach allows examining whether embodied language mechanisms remain operative despite the conflation of processes typical of daily verbal activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To address both questions, we implemented a videogame-based motor training protocol and assessed the appraisal of actions in narratives through discourse-level processes subsuming multiple operations (e.g., word access, syntactic parsing, semantic integration, memory retrieval). Strategically, our intervention was aimed at dyslexic children, whose potential comprehension deficits 3 , 4 could give room to post-training improvements. As in previous research on text-level action appraisal 5 , our approach allows examining whether embodied language mechanisms remain operative despite the conflation of processes typical of daily verbal activity.…”
Section: Introductionmentioning
confidence: 99%
“…To test this notion, we assessed processing of information in two types of short stories –“action texts” (ATs) and “neutral texts” (NTs)– before and after motor training. We targeted dyslexic children, a population with intact motor abilities, potentially suboptimal comprehension skills 3 , 4 , and susceptibility to videogame-induced effects 15 . Our training protocol required participants to play whole-body AVGs on a Nintendo Wii, which allowed us to circumvent some of the artificial constraints characterizing classical paradigms in cognitive science (such as the continuous performance of a single motor action in the context of an otherwise static body).…”
Section: Introductionmentioning
confidence: 99%
“…Baddeley, 2000;Kibby & Cohen, 2008) and language comprehension (see e.g. Helland, 2007;Helland & Kaasa, 2005;Snowling, Bishop, & Stothard, 2000;Xiao & Ho, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Studies in alphabetic scripts have reported a functionally important phonological processing deficit in many dyslexics (Ramus, ; Ramus & Ahissar, ; Ramus, Marshall, Rosen, & van der Lely, ; Hoeft et al ., ; Shaywitz et al ., ; Boets et al ., ). In studies using Chinese characters, phonological problems were also found (Ho, Law, & Ng, ; Cheung et al ., ; Liu, Shu, & Yang, ), but these were not considered core deficits; rather, impairments in orthographic processing and morpheme awareness were thought to be more important (Ho, Chan, Tsang, & Lee, ; Ho, Chan, Lee, Tsang, & Luan, ; Chung, Ho, Chan, Tsang, & Lee, , ; Shu, McBride‐Chang, Wu, & Liu, ; Shu, Peng, & McBride‐Chang, ; Xiao & Ho, ).…”
Section: Introductionmentioning
confidence: 99%